Consolidation Analysis Using Preloading Combined with Prefabricated Vertical Drain At The Jakarta Cikampek II Selatan Phase II A - Raihan Fauzan Siregar; B.M.A.S. Anaconda Bangkara; Lydia Darmiyanti (President University, 2026)
The Jakarta–Cikampek II Selatan Phase II A toll road construction project on the STA 16+100–16+300 segment is faced with soft subgrade soil conditions identified through Dutch Cone Penetration Test results. These conditions can cause excessive settlement in the long term if not addressed, thus requiring effective soil improvement methods to accelerate the consolidation process. The commonly used repair method is preloading combined with Prefabricated Vertical Drain (PVD), because PVD functions to shorten the flow path of soil pore water, thereby accelerating the consolidation process. The analysis results show that the settlement that occurred is 0.31 m at STA 16+125 and 0.22 m at STA 16+250. The results of the preloading analysis without using Prefabricated Vertical Drain show that the time required to achieve 90% consolidation at STA 16+125 is 6.39 years with a settlement of0.28 m, and at STA 16+250, the time required is 5.60 years with a settlement of 0.20 m. Then, using the Prefabricated Vertical Drain combination preloading method, the time required to achieve 90% consolidation at STA 16+125 with a triangular pattern and a distance variation of 0.6-1.5 m is 2-13 days with settlement of 0.28-0.30 m, while with a square pattern with the same distance, the time required is 2-15 days with a settlement of 0.28-0.29 m. At STA 16+250, the time required to achieve 90% consolidation with a triangular pattern and a distance variation of 0.6-1.5 m is 7-53 days with settlement of 0.20 m, while with a square pattern with the same distance, the time required is 8- 61 days with settlement of 0.20 m.